Corporate governance practices and agency cost: evidence from Listed manufacturing firms in Sri Lanka - Kevin, J.; Keerthana, G.; Gand Balagobei, S. (17th International Research Conference on Management and Finance 2022, 2022)
Corporate governance deals with determining ways to take effective strategic decisions and develop added value to the stakeholders. This study aims to examine the influence of corporate governance practices on agency cost of listed firms in Sri Lanka. Secondary data covering seven year period from 2013 to 2019 was obtained from manufacturing firms listed in Colombo Stock Exchange (CSE). The study applies the governance practices such as board size, board independence, board meetings, and director ownership as a tool in monitoring agency costs based on asset utilization ratio as proxy for agency costs. The techniques of Pearson’s Correlation and Multiple regressions were employed in estimating the association between the corporate governance practices and agency cost. The empirical findings reveal that board independent directors statistically significant influence the agency cost of listed manufacturing firms in Sri Lanka whereas board size, board meetings and managerial ownership are not found to have a significant impact on agency cost. Therefore, there is strong evidence that board independent directors have a major effect as a device in mitigating agency costs. The results will support stakeholders, including corporate management, regulators, and investors to improve corporate governance mechanisms and make the effective decisions.
Keywords: Agency cost; Board Independence; Board size; Corporate governance practices